Aisyiyah dan Kiprahnya dalam Pembinaan Keluarga Sakinah - Adawiah, Rabiatul (Jurnal Muadalah, 2013)
Forming a happy family is not as easy as turning the palm of the hand , but a struggle that requires sacrifice and awareness is high enough. Women have an important position in the family life and was instrumental in creating a happy family. This study tried to describe about the pursuit of womens organizations that Sakinah Family Aisyiyah in coaching in South Kalimantan. The formulation of the problem studied is how the concept of harmonious family by Aisyiyah South Kalimantan , and how the pursuit of womens organizations in fostering harmonious family. The result showed that the concept of family Aisyiyah known as the "happy family" and gait Aisyiyah South Kalimantan region in fostering harmonious family is optimal, it can be seen from the development activities carried out by a happy family of five assemblies primarily sermons assembly with a happy family coaching program seed.Keywords: women, Aisyiyah, happy family .Membentuk keluarga sakinah tidak semudah membalik telapak tangan, namun sebuah perjuangan yang memerlukan pengorbanan dan kesadaran yang cukup tinggi. Perempuan mempunyai kedudukan penting di dalam kehidupan keluarga dan sangat berperan dalam mewujudkan keluarga sakinah. Penelitian ini mencoba mendeskripsikan tentang kiprah organisasi perempuan yaitu Aisyiyah dalam pembinaan Keluarga Sakinah di wilayah Kalimantan Selatan. Rumusan masalah yang diteliti adalah bagaimana konsep keluarga sakinah menurut Aisyiyah wilayah Kalimantan Selatan, dan bagaimana kiprah organisasi perempuan tersebut dalam pembinaan keluarga sakinah. Dari hasil penelitian didapatkan bahwa konsep Aisyiyah tentang keluarga dikenal dengan istilah âkeluarga sakinahâ dan kiprah Aisyiyah wilayah Kalsel dalam pembinaan keluarga sakinah cukup optimal, ini dapat dilihat dari kegiatan pembinaan keluarga sakinah yang dilaksanakan oleh lima majelis terutama majelis tabligh dengan pembinaan keluarga sakinah sebagai program unggulan.Kata kunci: perempuan, Aisyiyah, keluarga sakinah.